2015
DOI: 10.1007/s11239-015-1292-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of plasminogen and oxidized phospholipids bound to plasminogen distinguish between atherothrombotic and non-atherothrombotic myocardial infarction

Abstract: Oxidized phospholipids (OxPL) are abundant in atherosclerotic plaques. They are also bound to circulating plasminogen after myocardial infarction (MI), and their binding to plasminogen may accentuate fibrinolysis. We sought to assess whether circulating levels of plasminogen and OxPL bound to plasminogen (OxPL-PLG) increase following acute MI and whether this increase differs between atherothrombotic (Type 1) and non-atherothrombotic (Type 2) MI. We measured circulating levels of plasminogen and OxPL-PLG at 0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…For example, in a recent study,(39) we showed mean baseline levels of plasminogen and OxPL-PLG were lower in acute MI than in the stable CAD, consistent with prior data. (11) However, mean baseline levels of plasminogen and OxPLPLG were also lower in atherothrombotic versus non-atherothrombotic MI.…”
Section: Discussionsupporting
confidence: 91%
“…For example, in a recent study,(39) we showed mean baseline levels of plasminogen and OxPL-PLG were lower in acute MI than in the stable CAD, consistent with prior data. (11) However, mean baseline levels of plasminogen and OxPLPLG were also lower in atherothrombotic versus non-atherothrombotic MI.…”
Section: Discussionsupporting
confidence: 91%
“…A patient cohort was recruited to allow for determining the unique plasma metabolomic signature of AMI differentiated by proximate cause 14 . A novel criteria was developed for discriminating between thrombotic and non-thrombotic MI patients as widely accepted guidelines for such discrimination were unavailable.…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine changes in the plasma metabolome associated with myocardial infarction (MI) characterized by thrombotic etiology versus non-thrombotic etiology, DeFilippis and colleagues assembled a human cohort as previously described (DeFilippis et al, 2016;DeFilippis et al, 2017;Trainor et al, 2017). Briefly, 80 human subjects presenting with suspected acute MI or stable coronary artery disease (CAD) were enrolled.…”
Section: A Plasma Interactome For Stable Heart Diseasementioning
confidence: 99%